THE DEVELOPMENT OF ALBANIAN LEGISLATION AND THE CODIFICATION PROCESS DURING THE ZOGIST PERIOD - Jeta Goxha; Lindita Licaj (European Scientific Journal, ESJ, 2015)
The policy followed by Ahmet Zog during the years 1925-1939, is criticized in many aspects. There are different views about his contribution to the consolidation of the state. During these years the regime changes frequently forms by a Parliamentary Republic to a Monarchy. The main’s ally during this period was Italy. Regardless the underlying motives, we cannot denied the positive impact on the development of the Albanian legislation. This study is the result of a research on Italy's continued influence on Albanian Legislation. The main purpose of this paper is to present a brief overview of the development of the Albanian Legislation from 1925 until the beginning of the World War II. Zog was based on a detailed reform program to changes Albania by a backward country, in a European one. The essential step in the legislative policy of the Zog Kingdom was the creation of codes. During this period, the lawmaker was appointed to draft the Civil Code, the Penal Code and the Commercial Code inspired by Italian and French Codes. The publication in 1929 of the Civil Code, known as the Zog Code, has similarities with many other codes of countries of that time. The aim of this paper is to treat the legislative reforms introduced by Ahmet Zog and how they have influenced in the Albanian legal tradition. A legal tradition connected with the history of the country, the Albanian identity and being proud of its origins and history.